LESSONS IN HAND WASHING: INFLUENCE OF OCCUPATION, HABIT AND SANITATION ON THE TYPE AND BURDEN OF HAND MICROFLORA - Osayenum, Egwari Louis; Oluseun, Akinnola Olayemi; Warrie, Effiok William; Musbau, Kilani Adetunji; Chukwuma, Uzowuihe Xavier; Tolu, Adegbayi (International Journal of Research -GRANTHAALAYAH, 2021)
The hand is an important vehicle in disease transmission both in the healthcare setting and in communities. This study accessed the level of compliance to hand hygiene requirements among different professionals within and outside the hospital setting.in addition to the role of good hand hygiene practice in reducing the microbial population of hands. Structured questionnaire to access compliance by the various study group was analyzed statistically. Swabs of hands and contact surfaces were collected before and after different treatment application ranging from washing with soap, use of or a combination of treatment and assessed . Knowledge of the importance of hand hygiene did not translate to better hand hygiene practice among health workers compared to groups outside the health profession. There was a higher preference for water for anal cleansing after defecation as opposed to the use of tissue paper by male than female (p<0.05). The bacterial load in unwashed hands ranged from 106 CFU/ml for Proteus and Streptococcus species to 1010 CFU/ml for and Staphylococcus species. Hand washing without application of resulted in 1-2 log10 CFU reduction depending on bacterial species (p>0.05). Application of to unwashed hands resulted in 2-7 log10 CFU reduction for most bacterial species (p<0.05). Hands were re-colonized with same flora within one week of decolonizing. The multiple factors associated with re-colonization of decolonized hands pose the question as to how frequent should hands be washed?